Pendampingan Kegiatan Olimpiade Matematika (Cerdas Cermat Matematika) Antar Kelas SMP Citra Bakti - Bela, Maria Editha; Tali Wangge, Maria Carmelita; Wewe, Melkior; Lola, Teofania Kristina; Hari, Christina Lusiana (Abdimas Indonesian Journal, 2025)
The inter-grade Mathematics Olympiad (Cerdas Cermat Matematika) held at Citra Bakti Junior High School is a form of mentoring to improve the quality of mathematics learning and encourage the development of students' academic potential. This study aims to describe the implementation, impact, and effectiveness of this mentoring activity on students' academic and mental readiness. A qualitative approach was used, with data collection techniques including observation, interviews, and documentation. The activity took place on May 21, 2025, involving 12 seventh and eighth grade students divided into four groups. The results showed that the structured mentoring program improved students' understanding of mathematical concepts, self-confidence, and critical and logical thinking skills in a competitive atmosphere. Furthermore, this activity instilled character values such as cooperation, responsibility, sportsmanship, and discipline. The active involvement of teachers, student interns, and school support were key factors in the success of this program. Therefore, the school-level Mathematics Olympiad can serve as a good practice in strengthening academic culture and 21st-century learning, emphasizing mastery of material and the development of students' soft skills.